Students' Perception of Audio Visual in Teaching Listening Skills on the Second Grade Students of SMP Negeri 3 Majene - Putu Wahyu Sudewi; Nurul Fadilah (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Listening is the act of focusing on hearing something or the act of paying attention. Teaching listening skills to students who are learning English as a foreign language is a challenge for teachers. The purpose of this study was to determine students' perceptions of the use of audiovisual media in listening classes among the second-grade students of SMP Negeri 3 Majene. This study used qualitative research. Questionnaires and interviews served as the instruments. Findings showed that the students have a positive perception of audiovisuals because the use of audiovisuals in learning listening skills makes it easier for students to understand the material provided and interact with friends during the lesson. Audio-visual media is attractive, effective, relevant, and motivating for students in listening activities